PROFILE OF FEMUR FRACTURES IN THE ELDERLY (Fiep Bulletin - online, 2012)
The fractures of the femoral neck are a significant health problem, socioeconomic character, with emphasis on multiple causes falls and osteoporosis as the main responsible for the number of admissions for the elderly, hospital costs burdening the frequency. This study aims to present a profile of femoral neck fractures in the elderly in the city of João Pessoa - Brasil in 2009 and 2010. It is a documentary study consisting of the information found directly in the System of Health Indicators and Monitoring Politics for the Elderly (SISAPI) about the events on fractures of the femur in relation to: the number of admissions, proportion of admissions and rate of hospitalizations according to sex, years in the years 2009 and 2010, the city of João Pessoa - Paraíba, Brazil. It is noted in 2009 a greater number of hospitalizations in women with a ratio of 2.53 and hospitalization rate of 29.45, in 2010 the proportion of hospitalizations in women was 1.67 showing the prominent paired females . It is important to be alert to possible underreporting.
Keywords: Fracture; Femur; Hospitalization.